IDUA Gene Variants and Response to Zoledronic Acid Treatment in Chinese Women with Postmenopausal Osteoporosis - Lin H (Pharmacogenomics and Personalized Medicine, 2021)
Haiqing Lin,1 Jin Li,1 Zhonghua Xu,2 Ting Liu,3 Xindie Zhou3 1Department of Orthopedic Surgery, the Second Affiliated Hospital of Jiaxing University, Jiaxing, 314000, People’s Republic of China; 2Department of Orthopedics, Jintan Hospital Affiliated to Jiangsu University, Changzhou, 213200, People’s Republic of China; 3Department of Orthopedics, The Affiliated Changzhou No.2 People’s Hospital of Nanjing Medical University, Changzhou, 213003, People’s Republic of ChinaCorrespondence: Ting Liu; Xindie ZhouDepartment of Orthopedics, The Affiliated Changzhou No.2 People’s Hospital of Nanjing Medical University, Changzhou, 213003, People’s Republic of ChinaEmail 1418583360@qq.com; zhouxindie@njmu.edu.cnPurpose: Alpha-L-iduronidase (IDUA) rs3755955 and rs6831280 polymorphisms have been demonstrated to be associated with bone mineral density (BMD). However, no study has investigated the association of these two polymorphisms with osteoporosis (OP) susceptibility in Chinese postmenopausal women.Patients and Methods: IDUA gene polymorphisms were genotyped in 278 women with OP and 303 healthy controls via polymerase chain reaction and Sanger sequencing.Results: Our data indicated that IDUA rs3755955 and rs6831280 polymorphisms increased the risk of OP in homozygous, dominant, and allelic models. We observed lower lumbar spine BMD in younger women with the AA genotype of rs3755955 polymorphism. Finally, mutant genotypes with rs6831280 polymorphism were more sensitive to zoledronic acid treatment, and the treatment effect was significant in terms of BMD levels.Conclusion: In conclusion, IDUA rs3755955 and rs6831280 polymorphisms demonstrated susceptibility to OP in Chinese postmenopausal women. IDUA rs6831280 polymorphism caused differences in response to zoledronic acid treatment.Keywords: IDUA, polymorphism, zoledronic acid, postmenopausal osteoporosis